2007
DOI: 10.2807/esw.12.51.03336-en
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic infections in Europe: trends and figures - a summary of the EFSA-ECDC annual report

Abstract: The 2006 annual Community Summary Report from the European Food Safety Authority (EFSA) and the European Centre for Disease Prevention and Control (ECDC) was released this week with the latest trends and figures on the occurrence of zoonotic infections and agents, antimicrobial resistance and food-borne outbreaks in the then 25 European Union Member States and five non-EU countries (Bulgaria, Iceland, Liechtenstein, Norway and Romania).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The incidence of non-foodborne infections in the UK is estimated at around 4.5 million cases per year, the largest proportion of which are norovirus infections transmitted easily from person to person within community groups [18]. The Zoonoses Report published by EFSA and the European Centre for Disease Prevention and Control (ECDC) in 2007 estimated that one third of the populations in developed countries are affected by foodborne diseases every year [19,20]. In a 1999 review Sattar et al stated that as many as 99% of these infections go unreported because of the relatively mild symptoms; the true impact of foodborne illness is thus difficult to determine [21].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of non-foodborne infections in the UK is estimated at around 4.5 million cases per year, the largest proportion of which are norovirus infections transmitted easily from person to person within community groups [18]. The Zoonoses Report published by EFSA and the European Centre for Disease Prevention and Control (ECDC) in 2007 estimated that one third of the populations in developed countries are affected by foodborne diseases every year [19,20]. In a 1999 review Sattar et al stated that as many as 99% of these infections go unreported because of the relatively mild symptoms; the true impact of foodborne illness is thus difficult to determine [21].…”
Section: Discussionmentioning
confidence: 99%
“…2 Ó URBAN & VOGEL[9]. In the USA, the Foodborne Diseases Active Surveillance Network (FoodNet) collects data from ten States on diseases caused by enteric pathogens commonly transmitted through food.…”
mentioning
confidence: 99%
“…These results were consistent with results reported by the US Food and Drug Administration report 45 where percentages of resistance were greater in isolates of veterinary origin than those from human origin. Similarly, Denny et al 9 found that all S. Enteritidis isolates from humans in Europe were sensitive to all tested antimicrobials including nalidixic acid, sulphonamides, and ampicillin. In contrast, Fernandez et al 35 reported that S. Enteritidis isolates from hospitalized patients in Brazil exhibited a broader spectrum of antibiotic resistance profiles than the non-human isolates.…”
Section: Discussionmentioning
confidence: 86%
“…respectively. 9,10 Within the genus Salmonella, S. Enteritidis and S. Typhimurium serovars are considered the major etiologic agents of foodborne illnesses. 11 Poultry products still represent one of the major sources of salmonellosis worldwide 12 with horizontal transmission as the major contributing factor of Salmonella contamination of the poultry products and their processing plants.…”
Section: Comparative Analysis Of Virulence and Resistance Profiles Ofmentioning
confidence: 99%